Recurrent encephalopathy and hyperammonemia in new born: case of arginosuccinic aciduria - Singh, Parminder; Gupta, Divya (International Journal of Contemporary Pediatrics, 2018)
Urea cycle disorders result from defects in the metabolism of waste nitrogenous compounds derived from the breakdown of proteins and other nitrogen-containing molecules. Argininosuccinic aciduria is a rare autosomal recessive heterogeneous urea cycle disorder, which leads to the accumulation of argininosuccinic acid in the blood and urine. It is caused by defect in the argininosuccinate lyase (ASL) gene, which regulates the breakdown of argininosuccinate to fumarate and arginine in the urea cycle. They are a heterogeneous group of disorders which are associated with hyperammonemia resulting in severe neurological dysfunction like encephalopathy, seizures, developmental and psychomotor delay. The severe central nervous system dysfunction is by alteration of amino acid and neurotransmitters pathways and interference with normal cerebral energy metabolism and oxidative stress. Ammonium toxicity to the brain provokes irreversible damage due to cortical atrophy, edema, and demyelination, resulting in seizures, coma, and even death. We report such a case of urea cycle defect in a newborn that presented with recurrent encephalopathy with hyperammonemia precipitated by minor infections. Detailed investigations including genetic analysis lead to the diagnosis of argininosuccinic aciduria.